Differences in Anthropometric Characteristics and Body Composition between Rugby Players of National Team of Montenegro and National Team of Bulgaria - Pavle Malovic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this research was to determine the diff erences among the rugby players of national team of Montenegro and national team of Bulgaria in the morphological characteristics and body composition. A sample of 43 examinees is divided into two sub-samples. The fi rst sub-sample of the examinees consisted of 23 players of rugby national team of Montenegro, while the other sub-sample consisted of 20 players of rugby national team of Bulgaria. Morphological characteristics in the body composition were evaluated by a battery of 10 variables: body height, body weight, triceps skin set, biceps skin set, back skin set, abdominal skin set, thigh skin set, lower leg skin set, body mass index and muscle mass. The standard central and dispersive parameters of all variables are calculated. The signifi cance of the diff erences between the players of the two national teams in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was not found that the rugby players of the two mentioned national teams have statistically signifi cant diff erences in morphological characteristics and body composition.